2002
DOI: 10.1124/dmd.30.12.1378
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Reaction of Cisplatin with Thiols

Abstract: ABSTRACT:The reactions of cisplatin [cis-diamminedichloroplatinum(II), CDDP] with glutathione (GSH) and drug thiols were investigated at 37°C in 100 mM Tris-NO 3 , pH ϳ7.4, using a clinically relevant concentration of CDDP (33 ⌴), a large excess of GSH (16.5 mM), and [NaCl] of 4.62 mM. The conditions were designed to mimic passage of CDDP through the cytosol. The reactions were studied by UV-absorption spectroscopy, high-pressure liquid chromatography (HPLC), and atomic absorption spectroscopy. CDDP 1 exerts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Thus, this result is consistent with a mechanism by which cisplatin can perturb topoisomerase II function in situ. The ability of dithiothreitol to partially antagonize these effects can be explained from our spectrophotometric kinetic studies that showed that cisplatin reacted (half-time of 6 min) with dithiothreitol to form a complex similar to other sulfhydryl compounds (Ishikawa and AliOsman, 1993;Dabrowiak et al, 2002;Sadowitz et al, 2002). Using mixtures of untreated and cisplatin-treated kDNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, this result is consistent with a mechanism by which cisplatin can perturb topoisomerase II function in situ. The ability of dithiothreitol to partially antagonize these effects can be explained from our spectrophotometric kinetic studies that showed that cisplatin reacted (half-time of 6 min) with dithiothreitol to form a complex similar to other sulfhydryl compounds (Ishikawa and AliOsman, 1993;Dabrowiak et al, 2002;Sadowitz et al, 2002). Using mixtures of untreated and cisplatin-treated kDNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that agents that target protein sulfhydryl groups can act as either catalytic inhibitors or poisons of topoisomerase II␣. Because cisplatin is so reactive with free protein sulfhydryl groups (Ivanov et al, 1998;Dabrowiak et al, 2002;Sadowitz et al, 2002;Hagrman et al, 2003), we considered topoisomerase II␣ cysteines as possible sites responsible for the inhibition of the catalytic activity of topoisomerase II␣ observed in the presence of cisplatin. Our results using the fluorescent sulfhydryl-reactive reagent, ThioGlo-1 strongly suggested that cisplatin reacted with topoisomerase II␣ sulfhydryl groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, for the study of cisplatin, the columns of 25 cm had been employed. [15][16][17] For larger operations, shorter columns can be used to reduce the retention time of the compounds, while Rs in not significantly affected. In this study, the use of a shorter column is not necessary because an acceptable run time of analysis is obtained (< 6 min).…”
Section: Resultsmentioning
confidence: 99%